The Influence of Selected Flavonoids from the Leaves of Cirsium palustre (L.) Scop. on Collagen Expression in Human Skin Fibroblasts. (19th March 2014) - Nazaruk, Jolanta; Galicka, Anna
<x xml:space="preserve">Abstract</x> Ten flavonoids belonging to the subclasses of flavones, flavanones and aurones were isolated from methanolic extract of Cirsium palustre leaves after multistep chromatographic separation. Their structures were elucidated with spectroscopic methods. All compounds, except for luteolin 7‐O‐glucoside, were isolated for the first time. Four compounds—eriodictyol 7‐O‐glucoside (6), 6‐hydroxyluteolin 7‐O‐glucoside (11), scutellarein 7‐O‐glucoside (12) and pedalitin (14)—were tested for their effect on collagen expression in normal human dermal fibroblasts. Among them, compound 11 at 40 μM and compound 14, at all concentrations used (1, 20, 40 μM), significantly enhanced the level of total collagen secreted into the medium. Furthermore, compound 11 significantly stimulated type I collagen expression, whereas compound 14 activated type I and III collagen expression at the mRNA level, depending on concentration. MMP‐2 activity was inhibited by all study compounds, with the greatest effect recorded with compound 14 at 20 μM. The lack of effect on collagen content in the medium of compound 6‐ and compound 12‐treated cells, besides an increase in COL1A1 and COL1A2 expression, might be caused by diminished expression of HSP47 gene, resulting in decreased procollagen secretion. Future study of compounds 11 and 14 for their potential therapeutic use in conditions connected with collagen biosynthesis deficiency is required. Copyright © 2014 John Wiley & Sons, Ltd.